928 Can Medical Students Learn Urethral Catheterisation Through an Escape Room?. (19th August 2022) - Hanson, Mark; Coleburt, Damien; Badenoch, Thomas
Abstract: Aim: Escape rooms are an exciting way to learn through team-based challenges, particularly lending themselves to practical clinical skills. We sought to understand if escape rooms are beneficial for teaching urethral catheterisation to medical students. Method: 12 third year medical students were given an initial knowledge assessment, before completing the escape room in groups of three. The room consisted of a number of tasks including labelling anatomy, checking patient details, and gathering equipment, and culminated in successfully catheterising a model. On completion they were given a post escape room knowledge assessment, which was repeated two weeks later to assess retention. This was compared to a control group undertaking a traditional teaching method. Results: Initially, on a Likert scale of 1–5, 69% (n=9) stated that they were a 1 for confidence in performing a urethral catheterisation. After the escape room, all students recorded a 3 or 4, and two weeks later confidence remained at an average of 3 (n=8). 34.6% of questions were answered correctly in the pre assessment, improving to 90% at the post assessment, and two weeks later remained high at 84.1%. Conclusions: Students' knowledge of urethral catheters significantly improved following the escape room, mirrored by their increase in confidence. Despite having never observed or inserted a urethral catheter, all groups successfully catheterised the model, and found the active learning process more engaging.